Un train au pays des pick-ups : controverses et conflits autour du projet de grande vitesse ferroviaire en Californie - Charlotte Ruggeri (L'Espace Politique)
In 2008, the high-speed rail project was launched in California. Eleven years later, this project is at the heart of political controversies and conflicts are multiplying and are slowing down the progress of construction, which began in 2015. This article proposes to study the challenges of the Californian high-speed rail project, especially in the Central Valley. This project reflects the territorial representations associated with transport and mobility in California, but reveals also the difficulties of building major infrastructures projects in the United States. In a rather classic pattern, the opposition began with a political controversy, coupled with a territorial conflict. However, this conflict has gradually become a territorialization conflict. The protest is not united and its high dispersion makes actions ineffective, in a political context that is likely to weaken the project. Starting from the genesis of the Californian high-speed rail project, we will see how the political controversy surrounding it was formed and how since 2008, a territorial conflict emerged. Then, we will focus more specifically on the area of the Central Valley, where the opposition is ancient and strong, to see how the planning conflict has become a territorialization conflict, despite its limits. This article is based on a series of interviews conducted between 2013 and 2018, as well as a study of the Californian press.